Cloning and sequencing of a Treponema pallidum gene encoding a 31.3-kilodalton endoflagellar subunit (FlaB2). - Pallesen, L (1989)
A library of Treponema pallidum DNA was established in the direct selection vector pUN121. Six clones carrying a gene coding for a 33-kilodalton T. pallidum flagellum subunit were identified by colony hybridization with an oligodeoxynucleotide probe based on the N-terminal amino acid sequence of this subunit. An open reading frame of 286 amino acids with the expected N-terminal sequence and absence of cysteine residues was identified. The deduced protein had a calculated molecular weight of 31.3 kilodaltons. We propose to name this flagellar subunit FlaB2. FlaB2 shows a significant amino acid homology with flagellins of several remotely related bacterial species. This homology was most pronounced corresponding to the C-terminal and N-terminal parts of the protein, whereas the central region was variable.